Current Advances in Spinal Diseases of Elderly Patients - Hirai, Takashi; Nakashima, Hiroaki; Miyagi, Masayuki; Takahashi, Shinji; Uehara, Masashi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The rapid aging of populations in developed countries since the 2000s has placed increasing attention on the issue of musculoskeletal disorders in elderly patients. Notably, spinal disorders not only restrict the social activities of elderly patients, but they also lead to economic loss for society. "Current Advances in Spinal Diseases of Elderly Patients" is a topical collection of articles about current perspectives on diagnosis and treatment of spinal disorders including current surgical strategies. This Special Issue covers a broad range of issues, ranging from managing refractory states such as severe osteoporosis, spinal deformity, ossification of the spinal ligaments, and multiple arthropathy to managing lifestyle-related spinal diseases during the COVID-19 pandemic in elderly populations. We hope that the readers of this Special Issue find the contents interesting.